Gene discovery and functional marker development for fragrance in sorghum (Sorghum bicolor (L.) Moench) - Chutintorn Yundaeng (2018)
Key message: Sequence analysis and genetic mapping revealed that a 1,444 bp deletion causes a premature stop codon in SbBADH2 of sorghum IS19912. The non-function of SbBADH2 is responsible for fragrance in sorghum IS19912. 2-acetyl-1-pyrroline (2AP) is a potent volatile compound causing fragrance in several plants and foods. Seeds of some varieties of rice, sorghum and soybean possess fragrance. The genes responsible for fragrance in rice and soybean are orthologs that correspond to betaine aldehyde dehydrogenase 2 (BADH2). Genotypes harboring fragrance in rice and soybean contain a premature stop codon in BADH2 which impairs the synthesis of full length functional BADH2 protein leading to the accumulation of 2AP. In this study, we reported an association between the BADH2 gene and fragrance in sorghum. An F2population of 187 plants developed from a cross between KU630 (non-fragrant) and IS19912 (fragrant) was used. Leaves of F2and F3progenies were evaluated for fragrance by organoleptic test, while seeds of F2plants were analyzed for 2AP. The tests consistently showed that the fragrance is controlled by a single recessive gene. Gene expression analysis of SbBADH1 and SbBADH2 in leaves of KU630 and IS19912 at various stages revealed that SbBADH1 and SbBADH2 were expressed in both accessions. Sequence comparison between KU630 and IS19912 revealed a continuous 1,444 bp deletion encompassing exon 12 to 15 of SbBADH2 in IS19912 which introduces a frameshift mutation and thus causes a premature stop codon. An indel marker was developed to detect polymorphism in SbBADH2. Bulk segregant and QTL analyses confirmed the association between SbBADH2 and fragrance. © 2013 Springer-Verlag Berlin Heidelberg.